Hospital Location Selection Using Spherical Fuzzy TOPSIS - Kahraman, Cengiz; GÜNDOĞDU, FATMA KUTLU; Onar, Sezi Çevik; Öztaysı, Başar (Atlantis Press, 2019)
The three dimensional extensions of ordinary fuzzy sets such as intuitionistic fuzzy sets of type-2 (IFS2) or Pythagorean fuzzy sets (PFS), and neutrosophic sets (NS) aim at collecting experts' judgments more informatively and explicitly. In the literature, generalized three-dimensional spherical fuzzy sets have been introduced by Kutlu Gündoğdu and Kahraman [1]. In this paper, we develop and use spherical fuzzy TOPSIS and apply it to a hospital location selection problem.
Proceedings of the 11th Conference of the European Society for Fuzzy Logic and Technology, EUSFLAT 2019
Keywords: Fuzzy MCDM; Hospital Location Selection; Spherical Fuzzy Sets; TOPSIS